1977
DOI: 10.1149/1.2133353
|View full text |Cite
|
Sign up to set email alerts
|

AL/Si and Al/Poly‐Si Contact Resistance in Integrated Circuits

Abstract: This paper presents results on the effects of sintering temperature, sintering time, and contact geometry on Al/Si and Al/poly‐Si contact resistance. At sintering temperatures >450°C the resistance of p‐type contacts is virtually constant and independent of time. The resistance of n‐type contacts, particularly to poly‐Si, increases with increasing sintering temperature for T>450°C . This is attributed to the precipitation of a p‐type (Al‐doped) layer on n‐contacts during sintering. The interface resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…Although the MXene materials do not possess such a high surface area as electric double-layer capacitor (EDLC) materials, 6,11,24,35,36 they are suggested to employ the energy storage through pseudocapacitive ion intercalation route giving rise to high capacitance and attractive electrochemical properties without the need for a high surface area.…”
Section: 34mentioning
confidence: 99%
See 3 more Smart Citations
“…Although the MXene materials do not possess such a high surface area as electric double-layer capacitor (EDLC) materials, 6,11,24,35,36 they are suggested to employ the energy storage through pseudocapacitive ion intercalation route giving rise to high capacitance and attractive electrochemical properties without the need for a high surface area.…”
Section: 34mentioning
confidence: 99%
“…Lukatskaya et al 38 indicated that the capacitance comes mainly from pseudocapacitive redox reactions of the Titanium. Gogotsi and co-workers 35,39 studied MXene as an anode material for Li-ion batteries (LiBs) and asymmetric cells and suggested the following lithiation and delithiation reactions taking place when Li + ions are inserted into the MXene matrix as described in Equation 1.Ling et al 23 and Zhao et al 38 also showed that expanding the interlayer gaps improves the capacity by facilitating ion transport. MXene combined with nanocarbons 12,14,23,30,40,41 and polymers 17,23 were shown to yield better capacitance than pristine MXene but in a narrow voltage window (<1.0 V) in aqueous electrolytes 17,26,[28][29][30]41 or higher voltage window (>1.0 V) in organic electrolyte.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 Following the deposition of Al layer on the silicon substrate by a sintering treatment at 450 o C, Al can be doped into the silicon at the Al/Si interface as acceptor impurities by dissolution and recrystallization of silicon. 12 The specific contact resistivity better than 10 −4 Ω·cm 2 can be easily achieved. 13 applied to n-type silicon (n-silicon) as easily as Al to p-silicon.…”
Section: Introductionmentioning
confidence: 99%